Race and Adult Education: A Critical Review of the North American Literature - Juanita Johnson-Bailey; Ronald M. Cervero (Adult Education Research Conference, 2000)
The paper critically evaluates the North American literature showing how race has been treated historically and presents three perspectives on race that inform contemporary research.